Temporary shocks and offshoring: the role of external economies and firm heterogeneity - Devashish Mitra; Priya Ranjan (Institute for the Study of Labor (IZA), 2007)
We construct a model of offshoring with externalities and firm heterogeneity. Due to the presence of externalities, temporary shocks like the Y2K problem can have permanent effects, i.e., they can permanently raise the extent of offshoring in an industry. Also, the initial advantage of a country as a potential host for outsourcing activities can create a lock in effect, whereby late movers have a comparative disadvantage. Furthermore, the existence of firm heterogeneity along with externalities can help explain the dynamic process of offshoring, where the most productive firms offshore first and the others follow later. Finally, we work out some unexpected welfare implications which show that net industry profits can be lower in an outsourcing equilibrium than in a regime of no outsourcing. Consumer welfare rises, and under fairly plausible conditions this effect can offset the negative impact on profits.
urn:nbn:de:101:1-20080401190
Keywords: 330; Offshoring; Outsourcing; Externer Effekt; Schock; Nord-Süd-Beziehungen; Direktinvestition; Wohlfahrtseffekt; Theorie; Industriestaaten; Entwicklungsländer